2012
DOI: 10.3844/ajassp.2012.399.404
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Micro-Channel Heat Sink with Dimpled Surfaces

Abstract: Problem statement: The power density of electronic devices has been increasing along with the rapid technology development. Cooling off electronic systems is essential in controlling the component temperature and avoiding any hot spot. The micro-devices are now extensively used in electronic application especially for cooling the computer chip. Approach: Micro-channel heat sinks are adopted in electronics cooling together with different technologies to enhance the heat transfer process. To improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Gururatana [29] also showed that Nu could be enhanced using dimpled structure but it was found useful for Re more than 125. Liu et al [30] used different grooved microstructures and observed that Nu for V-grooved structure was 1.5 times more than that for other structures considered.…”
Section: Introductionmentioning
confidence: 99%
“…Gururatana [29] also showed that Nu could be enhanced using dimpled structure but it was found useful for Re more than 125. Liu et al [30] used different grooved microstructures and observed that Nu for V-grooved structure was 1.5 times more than that for other structures considered.…”
Section: Introductionmentioning
confidence: 99%